Beekeeping in Tamaulipas, a very sweet and nutritive activity - González-Rodríguez, Laura Elena (Universidad Autónoma de Tamaulipas, 2010)
This study first addresses the situation of beekeeping in different areas, both global, national and regional level. Mexico ranks fifth in production of honey in the world and ranks third in exports. In Mexico, most honey production is concentrated in the southeastern states in the state of Tamaulipas has been an ever increasing this activity, has a record of 350 producers and 22,000 hives, of which 11.000 are intended to services pollination of crops according to preliminary figures from the Sagarpa, honey production in our state is of 716 tons per year. Therefore, the Institute for Applied Ecology is conducting a Sustainable Land Beekeeping supported by the Fundacion Produce Tamaulipas AC. The aim is to diagnose the real situation of beekeeping in our state, get a census of producers involved in this activity and know the amount of honey they produce. Preliminary results indicate that so far, there have been 83 and 175 beehives producers operating in the central and southern Tamaulipas. It has an inventory of 33 species of wild plants that are visited by bees, of which 12 species produce nectar, pollen produced eight and 13 produced both resources.